2021
DOI: 10.1111/inr.12650
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ ehealth literacy and associations with the nursing practice environment

Abstract: Aim To report on ehealth literacy levels in nurses and to explore its associations with the nursing practice environment. Background Nurses increasingly use the Internet and associated technologies to seek health‐relevant information and manage their health. Introduction High ehealth literacy is a predictor of better health outcomes in diverse populations but its levels and work‐related determinants have not been adequately explored in direct‐care nurses. Methods The sample for this cross‐sectional study consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 41 publications
1
17
0
2
Order By: Relevance
“…A total of 1304 studies were identified from literature searches, of which 26 met the inclusion criteria (Figure 1). The majority were cross-sectional studies, of which 11 [24][25][26][27][28][29][30][31][32][33][34] were considered prevalence data studies, and 13 [35][36][37][38][39][40][41][42][43][44][45][46][47] as analytical cross-sectional studies (Table 1). Among the remaining ones, 2 were experimental studies [48,49].…”
Section: Main Characteristics Of Studies Identifiedmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 1304 studies were identified from literature searches, of which 26 met the inclusion criteria (Figure 1). The majority were cross-sectional studies, of which 11 [24][25][26][27][28][29][30][31][32][33][34] were considered prevalence data studies, and 13 [35][36][37][38][39][40][41][42][43][44][45][46][47] as analytical cross-sectional studies (Table 1). Among the remaining ones, 2 were experimental studies [48,49].…”
Section: Main Characteristics Of Studies Identifiedmentioning
confidence: 99%
“…Among the remaining ones, 2 were experimental studies [48,49]. The studies included were conducted over a wide range of years, from 1999 [25] to 2021 [27], and more than 65% (17/26) of them [26][27][28]32,33,35,37,39,40,42,44] have been published in the last 5 years.…”
Section: Main Characteristics Of Studies Identifiedmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, given the complicated techniques that may pertain to the use of hardware and software systems, using online information to manage health has been reported as a source of frustration for medical professionals. 43 , 44 Additionally, web-based information is reported to both alleviate and sometimes increase stress, depending on the reliability of the information source and the way the information is used. 45 Thus, although the Internet has become the main source of mental health information worldwide, the lack of proper regulation means that its quality remains questionable, and it is difficult to judge the reliability of health information on the Internet.…”
Section: Introductionmentioning
confidence: 99%